Subcellular Compartmentation of Alternatively Spliced Transcripts Defines SERINE/ARGININE-RICH PROTEIN30 Expression . Issue 4 (1st March 2018) - Hartmann, Lisa; Wießner, Theresa; Wachter, Andreas
Abstract : Differential compartmentation and translation of alternatively spliced transcripts adjusts expression of the splicing regulator SR30 to ambient light conditions in Arabidopsis thaliana. Abstract: Alternative splicing (AS) is prevalent in higher eukaryotes, and generation of different AS variants is tightly regulated. Widespread AS occurs in response to altered light conditions and plays a critical role in seedling photomorphogenesis, but despite its frequency and effect on plant development, the functional role of AS remains unknown for most splicing variants. Here, we characterized the light-dependent AS variants of the gene encoding the splicing regulator Ser/Arg-rich protein SR30 in Arabidopsis ( Arabidopsis thaliana ). We demonstrated that the splicing variant SR30.2, which is predominantly produced in darkness, is enriched within the nucleus and strongly depleted from ribosomes. Light-induced AS from a downstream 3′ splice site gives rise to SR30.1, which is exported to the cytosol and translated, coinciding with SR30 protein accumulation upon seedling illumination. Constitutive expression of SR30.1 and SR30.2 fused to fluorescent proteins revealed their identical subcellular localization in the nucleoplasm and nuclear speckles. Furthermore, expression of either variant shifted splicing of a genomic SR30 reporter toward SR30.2, suggesting that an autoregulatory feedback loop affects SR30 splicing. We provide evidence that SR30.2 can be further spliced and, unlike SR30.2, the resulting cassette exon variant SR30.3 is sensitive to nonsense-mediated decay. Our work delivers insight into the complex and compartmentalized RNA processing mechanisms that control the expression of the splicing regulator SR30 in a light-dependent manner.